2018
DOI: 10.1139/cjp-2017-0750
|View full text |Cite
|
Sign up to set email alerts
|

Current status of Turkish accelerator and radiation laboratory in Ankara: the TARLA facility

Abstract: The Turkish Accelerator and Radiation Laboratory in Ankara, abbreviated as the TARLA facility, is proposed as the first facility of Turkish Accelerator Center (TAC) project. TARLA is under construction in Golbasi campus of Ankara University by coordination of the Institute of Accelerator Technologies (IAT). TARLA is designed to generate free-electron laser (FEL) pulses in mid- and far-infrared regions as well as Bremsstrahlung radiation up to 30 MeV. TARLA is based on superconducting electron accelerators to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Therefore, design and production stages are key to achieve these requirements. In this study, optimization methods are applied on the following basic formulas to find geometric features of the BPMs for Turkish Accelerator and Radiation Laboratory in Ankara (TARLA) [8].…”
Section: Bpm Antenna Designmentioning
confidence: 99%
“…Therefore, design and production stages are key to achieve these requirements. In this study, optimization methods are applied on the following basic formulas to find geometric features of the BPMs for Turkish Accelerator and Radiation Laboratory in Ankara (TARLA) [8].…”
Section: Bpm Antenna Designmentioning
confidence: 99%
“…With beam dynamics simulation it was found that five solenoid magnets would be sufficient for transporting the beam through the injector [2,3]. The axis of the beamline just after gun has a bend about 15…”
Section: Tarla Injectormentioning
confidence: 99%
“…The Turkish Accelerator and Radiation Laboratory in Ankara (TARLA), which has had continuous support from the Turkish Ministry of Development (TMD) since its conception in 2006, is designed as a multi-experiment facility providing a variety of accelerator-based radiation sources for users from various fields [1,2]. Based on a state-of-the-art superconductor technology, the current scope of the TARLA accelerator is designed to drive two free-electron laser (FEL) beamlines covering the range of 3-250 µ m and one Bremsstrahlung line providing gamma radiation in the range of 1-30 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this compression process, these cavities are also called as bunch compressors. When the installation of the injector is completed, the TARLA injector line will deliver electrons with bunch length of ∼0.4-6 ps at the operation frequency of 1.3 GHz [4,5].…”
Section: Introductionmentioning
confidence: 99%